(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Phytochemicals are present in medicinal plants. Costus igneus is used as a medicinally important plant for its anti-diabetic property. The purpose of the current study was to choose the best extraction solvent. The powder of roots, stem and leaves were separately extracted with different solvents like ethanol, methanol, chloroform, acetone and distilled water. Tannins, phlobatannins, alkaloids, phenols, saponins, flavonoids, terpenoids, triterpenes, steroids, cardiac glycosides, proteins, carbohydrates, reducing sugars were present in roots, leaves and stem of Costus igneus. Ethanolic extract shows most of the phytochemicals are present in Costus igneus.